Determination Of Leading Vegetable Commodities - Maure, Gerson Hans; Timung, Andri P; Maitia, Jitro A; Malese, Frengki I (JURNAL AGRIBISAINS, 2025)
The Tanglapui area is an agricultural area that has never been identified as a superior commodity since its establishment and its development and sustainability have been considered. Vegetables are one of the agribusiness sectors that play a role in improving people's welfare and income. To determine the potential of superior vegetable commodities, SLQ and DLQ analysis were carried out. The data used in this analysis is the time series data of vegetable production in 2019-2023 in Alor Timur District and Alor Regency obtained from the Alor Regency Agriculture and Plantation Service. Superior commodities are selected based on the results of SLQ and DLQ calculations with a value > 1, superior commodities are commodities that have the most potential to be developed and can spur economic growth. The results of the study obtained that the basic vegetable commodities in the Tanglapui area are shallots, tomatoes, eggplants, beans, cucumbers and chayote, while the superior vegetable commodities are shallots, tomatoes, eggplants, beans and chayote. While cabbage, carrots, mustard greens, long beans, chilies, cucumbers, kale and spinach are the mainstay commodities.